How to resolve zip injury of prepuce? Better way of manipulation - Thakkar, Nimesh; Patel, Pranav; Patel, Nirav (International Surgery Journal, 2019)
Background: Entrapment of prepuce in a zipper is a common cause of prepuceal injury in children. It is seen in boys of age group 5-12 years who usually do not wear underpants. About 80% of these injuries occur accidentally while zipping up. Methods: We reported 20 cases with zipper injury during our study period, which were divided in two groups. In Group A, Patients were managed by conventional techniques while in Group B; we managed patients with our technique of manipulation. Final Outcomes were compared with need of circumcision. Results: All patients in this study were male patients. All were from pediatric age group, except one case in Group A was Adult. In Group A, 7 patients (70%) required Circumcision while in Group B study, only 1 patient (10%) required circumcision. Moreover we found this technique more Simple and Easy. Conclusions: We found this technique very easy, less time consuming, less trauma to prepuce and need of Circumcision is less with this manipulation.